DISTRIBUSI KOMODITAS ANDALAN SUBSEKTOR PERIKANAN BERBASIS POTENSI WILAYAH DI KABUPATEN BANYUMAS JAWA TENGAH - Tobari Tobari (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2009)
Fishery subsector plays role in providing food, raw material for industry, workfield, and also national revenue. Therefore, government has to concern about increasing the production intensity of fishery subsector. Banyumas Regency is one of region that has potency as center of fishery production in Central Java. The aim of this research were: 1) to know potency of commodity of fishery subsector from concentration and specialization level; and 2) to know area that has good growth and competitive advantage. Result of research showed that: 1) nilam, karper and nila/mujair fishes were basis commodity in Banyumas Regency from its concentration and specialization level; and 2) areas that good potency for developing nilam, karper and nila/mujair fishes as superior commodity were subdistrict of Lumbir, Wangon, Jatilawang, Rawalo, Tambak, Somagede, Kalibagor, Banyumas, Purwojati, Ajibarang, Gumelar, Pekuncen, Purwokerto Selatan, Purwokerto Barat and Purwokerto Utara. These subdistrict had good growth and competitive level rather than others in Banyumas Regency. Key words : fishery subsector, basis commodity, superior, competitive